Immunomodulatory Drugs: IMiDs in Acute Myeloid Leukemia (AML) - F. Zeidner, Joshua; C. Foster, Matthew (Current Drug Targets, 2017)
AML patients have an aberrant and dysfunctional immune state, paving the way for novel agents targeting pathways that integrate with immune signaling, function, and response. Small molecule immunomodulatory drugs (IMiDs) represent a class of agents derived from the parent compound, thalidomide. There are currently 3 IMiDs approved for a variety of malignancies: thalidomide, lenalidomide, and the newest agent, pomalidomide. IMiDs lead to a multitude of immunobiologic effects such as cytokine modulation, co-stimulation of T cells, down-regulation of co-inhibitory molecules, enhancing natural killer cell activity, inhibition of regulatory T cells, and repairing perturbed synapse formation on T cells. IMiDs have been extensively studied in various AML settings with promising clinical activity. This review discusses the immunologic effects of IMiDs, the rationale for studying IMiDs in AML, and the published and ongoing clinical trials investigating IMiD activity in AML.
Keywords: thalidomide